CGGAN: a context‐guided generative adversarial network for single image dehazing. Issue 15 (18th February 2021) - Zhou, Zhaorun; Shi, Zhenghao
Abstract : Image haze removal is highly desired for the application of computer vision. This study proposes a novel context‐guided generative adversarial network (CGGAN) for single image dehazing. Of which, a novel new encoder–decoder is employed as the generator. In addition, it consists of a feature‐extraction net, a context‐extraction net, and a fusion net in sequence. The feature‐extraction net acts as an encoder, and is used for extracting haze features. The content‐extraction net is a multi‐scale parallel pyramid decoder and is used for extracting the deep features of the encoder and generating coarse dehazing image. The fusion net is a decoder and is used for obtaining the final haze‐free image. In order to get better dehazing results, multi‐scale information obtained during the decoding process of the context extraction decoder is used for guiding the fusion decoder. By introducing an extra coarse decoder to the original encoder–decoder, the CGGAN can make better use of the deep feature information extracted by the encoder. To ensure that the proposed CGGAN works effectively for different haze scenarios, different loss functions are employed for the two decoders. Experiments results show the advantage and the effectiveness of the proposed CGGAN, evidential improvements over existing state‐of‐the‐art methods are obtained.